1993
DOI: 10.1007/bf01383736
|View full text |Cite
|
Sign up to set email alerts
|

Australian academics: Career patterns, work roles, and family life-cycle commitments of men and women

Abstract: Abstract. Men and women who held a full-time appointment at lecturer level and above in Australian universities in 1988 were compared in terms of the career paths they had followed, geographic mobility, domestic responsibilities, work roles, and levels of performance as an academic. Women had more often spent a period outside the workforce or in part-time employment due to childcare responsibilities. They more frequently had followed their partners to another city or country, they more often had been a tutor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Compared to male academics female scientists more frequently follow their partners to another city or country (Bronstein, 2001;Ledin, Bornmann, Gallon & Wallon, 2007). In addition male scientists often report that their wives had followed them as a consequence of their changing jobs while this is rarely the case for female academics (Romanin & Over, 1993). Traditional gender roles are still prevalent and independently of the educational and professional status of the spouse her mobility is more 'tied' to that of their male partner than vice versa (Ackers, 2004).…”
Section: Linked Lives -Tied Migrationmentioning
confidence: 99%
“…Compared to male academics female scientists more frequently follow their partners to another city or country (Bronstein, 2001;Ledin, Bornmann, Gallon & Wallon, 2007). In addition male scientists often report that their wives had followed them as a consequence of their changing jobs while this is rarely the case for female academics (Romanin & Over, 1993). Traditional gender roles are still prevalent and independently of the educational and professional status of the spouse her mobility is more 'tied' to that of their male partner than vice versa (Ackers, 2004).…”
Section: Linked Lives -Tied Migrationmentioning
confidence: 99%
“…As a result, women are disadvantaged through being less likely than men to have overseas qualifications and experience (see Gale 1980). Consistent with the proposition that family life-cycle commitments inhibit the career development of women more than men, women in tenure-level positions in Australian universities are considerably less likely than male academics or than women in the population in general to be married or to have children (see Romanin and Over 1993).…”
mentioning
confidence: 53%
“…At the time of initial appointment fewer than 40% of the men and the women was a parent. In a survey of Australian academics, Romanin and Over (1993) found that women at lecturer level and above were substantially more likely than their male colleagues not to have had children or to have experienced career interruption (a period in part-time employment or outside the workforce) in providing child care. The cost of career development for many women is to remain childless.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations